Managing Institutional Image through Creative Public Relations: A Case Study of TABA Courses in a Pesantren in Situbondo: Manajemen Citra Lembaga melalui Hubungan Masyarakat Kreatif: Studi Kasus Kursus TABA di Pesantren di Situbondo - Zahrotul Widad; Abdul Goffar; Akhmadi (Mapendis: Jurnal Manajemen Pendidikan Islam, 2024)
This study examines how creative public relations are implemented through the TABA (Tajwid and Language) course program in managing the institutional image of a pesantren in Situbondo, Indonesia. Pesantren, as indigenous Islamic educational institutions, face increasing demands to maintain public trust and social relevance amid changing educational expectations. Using a qualitative field research approach, this study explores how educational programs function as strategic communication practices rather than mere promotional activities. Data were collected through in-depth interviews, participant observation, and documentation involving pesantren leaders, public relations staff, santri, and community participants. The findings reveal that the TABA course program operates as an effective form of creative public relations by embedding communication within substantive educational practice. Openness to community participation, the involvement of santri as instructors, and sustained interaction between the pesantren and the public contribute significantly to the formation of a positive institutional image. Public perceptions of the pesantren are shaped through direct experience, leading to increased trust, accessibility, and recognition of the pesantren as an inclusive and socially responsive educational institution. The study also finds that public relations in pesantren contexts functions most effectively when aligned with core educational missions and values. Rather than relying on formal promotion, institutional image is constructed through consistent educational engagement and visible outcomes. This research contributes to the field of Islamic educational management by highlighting the role of creative, program-based public relations strategies in strengthening pesantren legitimacy and community relations.